2015
DOI: 10.5798/diclemedj.0921.2015.04.0601
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus is still the most common etiologic factor of liver cirrhosis: Results from a single center in Turkey

Abstract: Karaciğer sirozu sebepleri yönünden önlenebilir bir hastalık olduğu için epidemiyolojisinin araştırılması önemlidir. Biz bu tek merkezli çalışmada, Türkiye'nin Orta Anadolu bölgesinde, karaciğer sirozunun etyolojik nedenlerini ve epidemiyolojik özelliklerini belirlemeyi amaçladık.Yöntemler: 1 Ocak 2011 ve 31 Eylül 2014 tarihleri arasında sağlık merkezimizdeki yataklı ve ayaktan kliniklere başvurmuş olan karaciğer sirozu tanılı hastalar kaydedildi.Bulgular: Toplam 135 hasta çalışmaya dahil edildi: ortalama yaşı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
2
1
0
3
Order By: Relevance
“…The number of male patientswere more than women. This is in accordance with several previous studies which stated that there were more people with cirrhosis of the liver with HBV infection in men than in women [25][26][27] . This is due to the protective role of estrogen for the liver.…”
Section: Discussionsupporting
confidence: 94%
“…The number of male patientswere more than women. This is in accordance with several previous studies which stated that there were more people with cirrhosis of the liver with HBV infection in men than in women [25][26][27] . This is due to the protective role of estrogen for the liver.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that most liver cirrhosis patients with HBV infection in this study was male (80%). This is consistent with the demographic data in previous studies suggesting that patients with cirrhosis of the liver due to chronic HBV infection are more frequent men than women [13][14][15] . This may due to a protective role of estrogen that is prevents damage to the liver because estrogen inhibits the proliferation of hepatic stellate cells and fibrogenesis that play an important role in the course of cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
“…Kronik hepatit B enfeksiyonu karaciğer sirozunda halen en sık nedendir 4,12,13,14 . Karaciğer sirozunda karaciğer hemodinamik değişikliklerinin tesbiti erken tanı ve progresyonunun izlenmesinde önemli yeri vardır.…”
Section: Discussionunclassified